Plasticity of DNA methylation, functional brain connectivity and efficiency in cognitive remediation for schizophrenia. (July 2020) - Ho, New Fei; Tng, Jordon Xin Jie; Wang, Mingyuan; Chen, Guoyang; Subbaraju, Vigneshwaran; Shukor, Suhailah; Ng, Desiree Si Xian; Tan, Bhing-Leet; Puang, Shu Juan; Kho, Sok-Hong; Siew, Rachel Wan En; Sin, Gwen Li; et al.
Abstract: Cognitive remediation (CR) is predicated on principles of neuroplasticity, but the actual molecular and neurocircuitry changes underlying cognitive change in individuals with impaired neuroplastic processes is poorly understood. The present study examined epigenetic-neurocircuitry-behavioral outcome measures in schizophrenia, before and after participating in a CR program that targeted higher-order cognitive functions. Outcome measures included DNA methylation of genes central to synaptic plasticity (CpG sites of Reelin promoter and BDNF promoter) from buccal swabs, resting-state functional brain connectivity and topological network efficiency, and global scores of a cognitive battery from 35 inpatients in a rehabilitative ward (18 CR, 17 non-CR) with similar premorbid IQ to 15 healthy controls. Baseline group differences between healthy controls and schizophrenia, group-by-time effects of CR in schizophrenia, and associations between the outcome measures were tested. Baseline functional connectivity abnormalities within the frontal, fronto-temporal and fronto-parietal regions, and trending decreases in global efficiency, but not DNA methylation, were found in schizophrenia; the frontal and fronto-temporal connectivity, and global efficiency correlated with global cognitive performance across all individuals. Notably, CR resulted in differential changes in Reelin promoter CpG methylation levels, altered within-frontal and fronto-temporal functional connectivity, increasing global efficiency and improving cognitive performance in schizophrenia, when compared to non-CR. In the CR inpatients, positive associations between the micro to macro measures: Reelin methylation changes, higher global efficiency and improving global cognitive performance were found. Present findings provide a neurobiological insight into potential CR-led epigenetics-neurocircuitry modifications driving cognitive plasticity.